FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN FACE TONER KOMBINASI EKSTRAK ETANOL DAUN MINT (Mentha piperita L.) DAN BUNGA TELANG (Clitoria ternatea L.) METODE DPPH - Afiyah, Azza Hasna; Listyani, Tiara Ajeng; Rahmatillah, Annie (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Mint leaves contain antioxidant compounds such as flavonoids, phenolic acids, triterpenes, vitamin C, provitamin A, mineral phosphorus, and iron. The telang flower plant is an anthocyanin antioxidant which includes natural antioxidants that have greater strength than vitamin C. The purpose of this study was to determine the antioxidant activity of a combination face toner preparation from mint leaf extract (Mentha piperita L.) and telang flower extract (Clitoria ternatea L.) DPPH method. The method used in this study was maceration extraction using 96% ethanol, preparation of the formulation by mixing mint leaf extract and butterfly pea flower extract, then adding Tween 80, glycerin, propylene glycol, nipagin, nipasol, and distilled water, stirring using a mortar and adding distilled water until reaching 100 ml. Following this, physical quality tests and physical quality data analysis were conducted using the Shapiro-Wilk test (SPSS) and antioxidant activity testing of the formulation using the DPPH method with a UV-Vis spectrophotometer. The overall physical quality test results showed good physical quality and met the physical quality test standards. The antioxidant test results for F1, F2, and F3 showed moderate antioxidant activity. The formula with good antioxidant activity was formula one with a concentration of (3:0.2), yielding a result of 115.55 ppm.